IoT-Based Smart Home System for LPG Leak Detection and Mitigation in Households Integrated with Blynk - Redistia Riding; Muhammad Muttaqin; Muhammad Zen (Jurnal Komputer Teknologi Informasi Sistem Komputer (JUKTISI), 2026)
Liquefied Petroleum Gas (LPG) is widely used as the primary energy source in Indonesian households; however, gas leakage poses a serious risk that may lead to fires and explosions if not detected at an early stage. This study aims to design and implement a smart home system based on the Internet of Things (IoT) for the detection and mitigation of LPG gas leaks in households integrated with the Blynk application. The research employed an experimental method by designing and testing a system using an ESP32 microcontroller, an MQ-2 gas sensor, a buzzer, LED indicators, and the Blynk application for remote monitoring and notifications. System testing was conducted in a real household environment with variations in the distance between the gas source and the sensor to evaluate sensor sensitivity, system response time, and IoT connectivity stability. The experimental results indicate that the system can effectively detect LPG gas leaks at an optimal distance of 5–15 cm, with an alarm response time of less than 2 seconds and an average Blynk notification delay of 2–3 seconds. In addition, the system demonstrated stable performance during continuous operation. Based on these results, the proposed system is considered effective, easy to implement, and has strong potential to enhance household safety against LPG gas leakage risks in Indonesia.